Seasonal modulation of M2 tide in the Northern Bay of Bengal. (1st April 2017) - Tazkia, A.R.; Krien, Y.; Durand, F.; Testut, L.; Islam, AKM S; Papa, F.; Bertin, X.
Abstract: The Northern Bay of Bengal (BoB) with its adjoining Ganges-Brahmaputra-Meghna delta (GBM) forms the largest deltaic region in the world. It is surrounded by a wide area of low-lying land (less than a few meters above mean sea level), very densely populated. It is home to a strong variability of sea level, across all timescales, with ample tides and frequent storm surges. It is also subject to extended river flooding during the monsoon season, with frequent overflows of two of the world's largest rivers (Brahmaputra and Ganges). There is thus a need to understand and predict the various mechanisms responsible for coastal and estuarine water level variability in this area. In this study, we address one of the least understood facets of this variability: the low-frequency modulation of tides. We focus on the seasonal changes of amplitude of the semi-diurnal lunar tide, M2. It is found that M2 amplitude shows marked changes between winter and summer seasons (of order 10 cm), incommensurate with most of the world's coastal ocean. We observe contrasted patterns from the open areas of the coastal ocean to the inner part of the GBM estuary. In the coastal ocean and over most of the GBM delta, M2 amplitude is stronger during summer and decreases until winter. Conversely, in the far northern part of GBM estuary, M2 amplitude is stronger during winter and weaker during summer. We make use of a hydrodynamic barotropic tidal model to decipher the processes responsible for this evolution. It is found that throughout the coastal ocean and over most of the GBM delta, this evolution is driven by frictional effects, with a seasonal modulation of bottom dissipation of tidal energy. Our simple barotropic model, however, does not capture the observed range of seasonal modulation of tides in the GBM estuary and at its mouth. Our study advocates for a careful consideration of these processes for a proper representation of the tidal dynamics as well as of the flooding hazard in the Bengal delta. Highlights: The Northern Bay of Bengal presents a very strong seasonal modulation of M2 tide amplitude. This seasonal signal extends from the coastal ocean to more than 100 km inland in the Ganges-Brahmaputra-Meghna delta. Higher tidal amplitude is seen in late sping-early summer, lowest amplitude is seen in winter. It is driven by the seasonal variability of oceanic steric height, through a modulation of frictional effects on the tidal currents.